Co-culturing Hyphomicrobium nitrativorans strain NL23 and Methylophaga nitratireducenticrescens strain JAM1 allows sustainable denitrifying activities under marine conditions - Alexandra Cucaita; Marianne Piochon; Richard Villemur (PeerJ, 2021)
Background Hyphomicrobium nitrativorans strain NL23 and Methylophaga nitratireducenticrescens strain JAM1 are the principal bacteria involved in the denitrifying activities of a methanol-fed, fluidized-bed marine denitrification system. Strain NL23 possesses the complete denitrification pathway, but cannot grow under marine conditions in pure cultures. Strain JAM1 is a marine bacterium that lacks genes encoding a dissimilatory nitrite (NO2−) reductase and therefore cannot reduce NO2−. Here, we report the characterization of some of their physiological traits that could influence their co-habitation. We also perform co-cultures to assess the potential synergy between the two strains under marine and denitrifying conditions. Methodology Anoxic planktonic pure cultures of both strains were grown with different concentrations of nitrate (NO3−). Anoxic planktonic co-cultures could only be cultured on low NaCl concentrations for strain NL23 to grow. Biofilm co-cultures were achieved in a 500-mL bioreactor, and operated under denitrifying conditions with increasing concentrations of NaCl. NO3− and NO2− concentrations and the protein content were measured to derive the denitrification rates. The concentrations of both strains in co-cultures were determined by quantitative PCR (qPCR). Ectoine concentration was measured by mass spectrometry in the biofilm co-culture. The biofilm was visualized by fluorescence in situ hybridization. Reverse-transcription-qPCR and RNA-seq approaches were used to assess changes in the expression profiles of genes involved in the nitrogen pathways in the biofilm cultures. Results Planktonic pure cultures of strain JAM1 had a readiness to reduce NO3− with no lag phase for growth in contrast to pure cultures of strain NL23, which had a 2-3 days lag phase before NO3− starts to be consumed and growth to occur. Compared to strain NL23, strain JAM1 has a higher µmax for growth and higher specific NO3− reduction rates. Denitrification rates were twice higher in the planktonic co-cultures than those measured in strain NL23 pure cultures. The biofilm co-cultures showed sustained denitrifying activities and surface colonization by both strains under marine conditions. Increase in ectoine concentrations was observed in the biofilm co-culture with the increase of NaCl concentrations. Changes in the relative transcript levels were observed in the biofilm culture with genes encoding NapA and NapGH in strain NL23. The type of medium had a great impact on the expression of genes involved in the N-assimilation pathways in both strains. Conclusions These results illustrate the capacity of both strains to act together in performing sustainable denitrifying activities under marine conditions. Although strain JAM1 did not contribute in better specific denitrifying activities in the biofilm co-cultures, its presence helped strain NL23 to acclimate to medium with NaCl concentrations >1.0%.